IFAE 2006 Incontri di Fisica delle Alte Energie - Italian Meeting on High Energy Physics - Pavia, Italy, 19-21 April 2006 - Montagna, G.; Nicrosini, O.; Vercesi, V.; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2007)
This book collects the Proceedings of the Workshop ``Incontri di Fisica delle Alte Energie (IFAE) 2006, Pavia, 19-21 April 2006". This is the fifth edition of a new series of meetings on fundamental research in particle physics and was attended by more than 150 researchers. Presentations, both theoretical and experimental, addressed the status of Standard Model and Flavour phyiscs, Neutrino and Cosmological topics, new insights beyond the present understanding of particle physics and cross-fertilization in areas such as medicine, biology, technological spin-offs and computing. Special emphasis was given to the expectations of the forthcoming Large Hadron Collider, due in operation in 2007. The venue of plenary sessions interleaved with parallel ones allowed for a rich exchange of ideas, presented in these Proceedings, that form a coherent picture of the findings and of the open questions in this extremely challenging cultural field.
Invited Talks -- Particle Physics: a Progress Report -- Getting Ready for Physics at the LHC -- Lattice QCD and Numerical Simulations -- The double life of the X meson -- Physics with Neutrino Beams -- Status and perspectives of Dark Matter and Astroparticle searches -- Future Perspectives of High Energy Experimental Physics and the Role of INFN -- Review Talks of Parallel Sessions -- Status of the Standard Model -- New physics -- Flavour Physics -- Neutrinos and Cosmic Rays: Session Summary -- Detectors and New Technologies -- Parallel Session: Standard Model Physics (P. Azzi and F. Piccinini, conveners) -- Theoretical progress in the muon g-2 -- Beyond leading-log approximation in the Parton Shower approach to Bhabha process -- Status and prospects of the measurement -- Recent Results from HERA -- Twistors and Unitarity -- Resummations in QCD: recent developments -- Resummation of Drell-Yan rapidity distributions -- Recent jet measurements at the Tevatron -- Vector Boson Production Associated with Jets @ LHC (ATLAS) -- Recent developments on precise electroweak observables -- W and Z bosons physics at LHC at low luminosity -- Electroweak corrections to the charged-current Drell-Yan process -- Single Top at Hadron Colliders -- Top physics at the LHC -- QCD corrections to Higgs physics at the LHC -- Standard Model Higgs Boson Searches at the Large Hadron Collider -- Parallel Session: New Physics (A. Perrotta and A. Strumia, conveners) -- Searching for extra-SUSY signals at LHC -- Search for New Physics at the Tevatron -- New physics searches in B meson decays -- Fermion mass in E 6 GUT with discrete family permutation symmetry S 3 -- Search for Supersymmetry with early ATLAS data -- Detection methods for long lived particles at the LHC -- A holographic composite Higgs model -- New Physics in Top Events at the LHC -- Searching for micro black holes at LHC -- Parallel Session: Flavour Physics (S. Giagu and L. Silvestrini, conveners) -- Lepton Flavor Violation and Rare Kaon Decays -- Neutral Kaon Physics at KLOE -- Charged kaons and V us at KLOE -- Rare decays at the B-Factories -- CP violation and CKM parameters determination in BaBar -- Semileptonic and nonleptonic decays of B c -- Aspects of non leptonic B s decays -- Measurement of the B s oscillation frequency at CDF -- Prospects for heavy flavor physics at LHC -- QED corrections and the B ? K? puzzle -- Status of the Unitarity Triangle analysis -- Non-perturbative inputs for Flavour Physics -- Bounds on the supersymmetric flavour space -- Parallel Session: Neutrinos and Cosmic Rays (E. Lisi and L. Patrizii, conveners) -- Neutrino oscillations with artificial sources -- Future measurements of neutrinos from the Sun, Earth and Supernovae -- Cosmology and Neutrinos, of fixed and variable mass -- Double Beta Decay Experiments -- Some Trends in Theoretical Models for Neutrino Masses -- Supernova neutrino burst as a probe of shock waves and matter density fluctuations -- Leptonic CP violation -- Neutrino astronomy with km3 underwater and under ice -- Ultra High Energy Cosmic Rays: Observations and Theoretical Aspects -- Recent Results in Gamma Ray Astronomy with IACTs -- Gamma-ray Astronomy with full coverage experiments -- Parallel Session: Detectors and New Technologies (A. Cardini, M. Michelotto and V. Rosso, conveners) -- The Liquid Xenon calorimeter of the MEG experiment -- The Silicon Vertex Trigger Upgrade at CDF -- Monolithic Active Pixel Sensors in a 130 nm Triple Well CMOS Technology -- The external scanning proton microprobe in Florence: set-up and examples of applications -- Infrastructure of the ATLAS Event Filter -- The CMS High-Level Trigger -- WLCG Service Challenges and Tiered architecture in the LHC era.
Keywords: Nuclear physics; Elementary particles (Physics).; Quantum field theory; Astrophysics; String theory; Heavy ions; Particle acceleration; Particle and Nuclear Physics; Elementary Particles, Quantum Field Theory; Astrophysics and Astroparticles; Quantum Field Theories, String Theory; Nuclear Physics, Heavy Ions, Hadrons; Particle Acceleration and Detection, Beam Physics